A dilatometric study of the effect of pressing on the kinetics of compression of ultrafine zirconium doxide powders under thermal annealing; Russian Physics Journal; Vol. 55, iss. 4 - Surzhikov A. P. Anatoly Petrovich (2012, 2012)
Title screen